Viúvas de maridos vivos: experiências e perspectivas de mulheres agricultoras familiares em Pinhão. - Tavares, Luzyanna Rocha (2016)
This dissertation aimed to know and analyze the daily life of women I call 'widows of living husbands', that is, family farmers whose spouses leave their farms and migrate to cities or neighboring states to Paraná to work in various activities without return agricultural duties for long periods. The research was developed in Pinhao municipality, region Paraná State Central West, with women involved in income generation projects developed by the Paraná Institute of Technical Assistance and Rural Extension (EMATER). There, the absence of their husbands because the need to rearrange the lives of these women farmers, forced to change their daily lives due to the different public and private settings, the division of labor by gender and other positive and negative consequences for themselves, for family and for the country life. In the context of family farming, they have to deal with gender relations, food production, environmental issues and sustainability of the properties and hence the relationship with one of the state agencies that is most close to them: EMATER. I sought to discuss this reality from the life stories told by some farmers, allowing reveal their expectations, their difficulties, their anxieties, in intersubjective exercise through the establishment of an oral history. Through its narratividades, there was an increase in responsibilities to the family, the activities of the property as well as the redefinition of roles traditionally occupied the property with the departure of their husbands. There was also the prospect of interaction with rural technical assistance and extension institutes, by binding to gender perspectives, has served for the construction of an empowerment perspective of these women and community development.